From ‘musique concrète’ and Acousmatic Art to the ‘New Music Theater’. The Austrian Composer Dieter Kaufmann - SZILÁGYI, Ana (Studia Universitatis Babes-Bolyai Musica, 2024)
This article follows the way the Austrian composer Dieter Kaufmann has gone with his conceptions taken from musical and extra-musical domains, as literature, visual arts, religion and politics, describing some of his theatrical works. For him the function of music is to improve the society and therefore his works are a critic to politics or to religion. Having studied in Paris by Olivier Messiaen, Pierre Schaeffer, François Bayle and René Leibowitz, he contributed to the development of the electronic music in Austria with his creation and his teaching of electroacoustic composition at the University of Music and Performing Arts in Vienna. He went further than the Parisian ‘musique concrète’, which worked with sound objects, and consciously selected and worked with objects of sound ambient in order to manage the sound environment, to musically shape it. The acousmatic art deals with sound objects, which are recorded and projected in another space, the theatre scene being an ideal space of it. A large part of his works are included in the genre of New Music Theater of the 20th and 21st century, where sound (tone and word) and movement come together, each of them having the same weight.